Racial Differences of Pigmentation in the Human Vestibular Organs. (September 2016) - Erbele, Isaac D.; Lin, Frank R.; Agrawal, Yuri; Francis, Howard W.; Carey, John P.; Chien, Wade W.
Objectives: Melanin pigmentation is present in the human inner ear. In this study, we quantify the melanin pigmentation in the vestibular system and examine racial differences of vestibular melanin pigmentation using human cadaveric temporal bone specimens. Study Design: Basic research. Setting: Laboratory. Subjects and Methods: Light microscopy was used to examine specimens from 40 left temporal bones from the Johns Hopkins Human Temporal Bone Collection. Color images of (1) ampulla of the horizontal canal, (2) utricular wall, (3) endolymphatic duct, and (4) posterior ampullary nerve as it enters the posterior canal were acquired with a digital camera attached to the microscope and image acquisition software. Acquired images of each anatomic area of interest were processed offline through ImageJ. Melanin content was then compared according to ethnicity, age, sex, and location. Results: Fifteen African American and 25 Caucasian specimens were analyzed. Mean age was 68.8 years. African American specimens had a significantly greater amount of pigment at all 4 sampled locations as compared with Caucasian specimens ( P < .01). Between sexes, there was a statistically significant difference ( P < .05) at the posterior ampullary nerve, with males having more than females. Melanin content was not associated with age. Conclusions: There is greater melanin pigmentation within the vestibular system of African Americans than in Caucasians, similar to what has been described in the cochlea. Racial differences in vestibular physiologic function have been observed in the literature and may be explained by differences in melanin pigmentation.